Development of a Clinical Teaching Unit in Internal Medicine to Promote Interprofessional and Multidisciplinary Learning: A Practical Intervention. Issue 1 (9th September 2020) - Hamoen, Esther C.; van Blankenstein, Floris M.; de Jong, Peter G. M.; Ray, Arghya; Reinders, Marlies E. J.
Abstract: Problem: Effective clinical workplace learning depends on interprofessional and multidisciplinary learning. However, traditional patient wards are centered around patient care and not so much around education. Other barriers such as time constraints also contribute to suboptimal interprofessional and multidisciplinary learning. Intervention: Six formal and informal learning activities that aimed at stimulation of interprofessional and multidisciplinary learning were designed and introduced in our patient ward to enable optimal integration of clinical practice and learning. Context: The study took place in an internal medicine inpatient ward where daily patient care is performed by specialized teams consisting of different healthcare professionals from the departments of Endocrinology, Nephrology, and Infectious Diseases. In the traditional ward setting, interprofessional and multidisciplinary learning mostly takes place during shared clinical activities. In this article, we describe the development and implementation of a Clinical Teaching Unit to support learning between different healthcare professionals. Impact: The intervention was evaluated with an online questionnaire among 108 nurses, student nurses, clerks, residents, supervising clinicians, and managers. Open-ended questions (response rate 65%) were used to determine the changes in the workplace experienced by the participants since the introduction of the Clinical Teaching Unit and what influenced their learning process and motivation to learn. Closed questions (response rate 46%) aimed to measure the effect of our intervention on collaboration, learning, and the quality of care and education. The results of the open-ended questions showed that participants experienced more interprofessional collaboration and learning. This took place in a less hierarchical, safer work climate which also resulted in perceptions of a better quality of patient care and education. The closed-ended questions showed that the intervention resulted in perceptions of improved collaboration, work culture, quality of care, education, and learning conditions. Lessons Learned: The findings imply that implementation of a Clinical Teaching Unit not only facilitates the integration of patient care and education but also the integration of different professions working together. From the intervention, we also learned that a successful Clinical Teaching Unit requires investment of time and staff, clear communication between healthcare professionals, and dedication of teachers within all professions.